American GI Forum 1992 - Meeting with Speaker John Florez - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of a 1992 National GI Forum Meeting with speaker John Florez, Executive Director of the White House Initiative on Education Excellence for Hispanic Americans. Also included is a video of a coronation of the 1992 San Jose American GI Forum Queen (52:42).